Mill+, an intuitive tool for simulating the milling process: Vibrations, cutting forces and surface quality control - Gorka Urbikain-Pelayo; Daniel Olvera-Trejo; Luis Norberto López de Lacalle; Alex Elías-Zuñiga; Itziar Cabanes (SoftwareX)
Machining is a highly technological manufacturing process for producing high-added value components across various engineering applications ranging from automotive to aerospace and medical devices. Especially in the machining of flexible components, vibrations remain a significant barrier to productivity, due to the lack of specific scientific understanding about the mechanics of the cutting process, tool-workpiece dynamics and the causes of unstable vibrations. While commercial software solutions exist, their cost and steep learning curve limit the access of small companies and researchers aiming to optimize machining dynamics. To address this gap, Mill+ provides a simple and intuitive solution to the time-delay dynamic equations that characterize milling systems with flexible features. The software generates stability diagrams based on typical milling parameters such as spindle speed, axial depth of cut and surface roughness predictions. Additionally, it offers insights into critical process variables, including cutting forces, power consumption, and material removal rates. This comprehensive visualization data enables users to make informed decisions about cutting parameters and predict outcomes without relying on the trial and error approach. Mill+ is designed for professional practitioners and postgraduate students to get started in machining vibrations.